2017
DOI: 10.1007/s10683-017-9544-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss aversion and the quantity–quality tradeoff

Abstract: Firms face an optimization problem that requires a maximal quantity output given a quality constraint. But how do firms incentivize quantity and quality to meet these dual goals, and what role do behavioral factors such as loss aversion play in the tradeoffs workers face? We address these issues with a theoretical model and an experiment in which participants are paid for both quantity and quality of a real effort task. Consistent with the basic economic theory, higher quality incentives encourage participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
(39 reference statements)
2
10
0
Order By: Relevance
“…Insofar as providing unsorted beans is indicative of cheating, we find the same. These findings complement Rubin et al (2018) who found that loss averse agents sacrifice quality for quantity, compared to agents who are not loss averse. We find that leveraging loss aversion through a clawback regime further induces loss averse agents to sacrifice quality for quantity.…”
Section: << Insert Table 3 About Here >>supporting
confidence: 83%
See 1 more Smart Citation
“…Insofar as providing unsorted beans is indicative of cheating, we find the same. These findings complement Rubin et al (2018) who found that loss averse agents sacrifice quality for quantity, compared to agents who are not loss averse. We find that leveraging loss aversion through a clawback regime further induces loss averse agents to sacrifice quality for quantity.…”
Section: << Insert Table 3 About Here >>supporting
confidence: 83%
“…That is, the incentive invites a shift towards low-expected returns, low-risk activities. In a lab setting with students solving simple math tasks, Rubin et al (2018) demonstrate that behavioral characteristics mediate the way that agents respond to quality-quantity incentives. Specifically, loss averse agents shift their attention from producing quality to producing quantity when quality is only weakly incentivized (even if it is observable to the principal).…”
Section: Introductionmentioning
confidence: 93%
“…Management research has found evidence of a tradeoff relationship between service quantity and quality in which increased effort placed on higher quality reduces the number of customers employees serve and vice versa (Förster et al 2003;Oliva and Sterman 2001;Wood and Locke 1990). A recent study (Rubin et al 2018) also found that loss aversion plays a role in the tradeoff between quantity and quality. Loss-avoidant participants shift their attention from quantity to quality when given a weak incentive.…”
Section: Introductionmentioning
confidence: 86%
“…Meanwhile, other has failed to detect a difference between the two frames (de Quidt et al, 2017;DellaVigna and Pope 2018;Grolleau et al, 2016). 2 A number of studies have considered the effects of different types of incentives for quality (Bracha and Fershtman 2013;Carpenter et al, 2010;Eckartz et al, 2012;Hammermann and Mohnen 2014;Rubin et al, 2018;Shurchkov 2012), while others have studied the effects of incentivising quantity on quality (Al-Ubaydli et al, 2015;Fest et al, 2019;Green, 2014;Greiner et al, 2011;Tonin and Vlassopoulos 2015). A few scholars have explored the relative effects and complementarity of incentives for quality and quantity (Kachelmeier et al 2008;Laske and Schröder 2017).…”
Section: Introductionmentioning
confidence: 99%